The influence of amaranth (Amaranthus hypochondriacus) dietary nitrates on the aerobic capacity of physically active young persons - Tomas Liubertas; Ramutis Kairaitis; Loreta Stasiule; Sandrija Capkauskiene; Arvydas Stasiulis; Pranas Viskelis; Jonas Viškelis; Dalia Urbonaviciene (Taylor & Francis Group, 2020)
Background Recent evidence indicates that elevating plasma nitrites through dietary nitrates (NO3 −) supplementation is associated with enhanced muscle efficiency, fatigue resistance and performance. Beetroot (in various forms) is the dominant source of dietary NO3 − primarily due to its vast availability and the simple form of preparation suitable for final consumption. After a few years of research and experimentation, our scientific team identified alternative source rich with dietary NO3 − as possible nitric oxide precursor, amaranth (Amaranthus hypochondriacus) with a standardized concentration 9-11% of NO3 −. This study aimed to evaluate the effect of single-dose (±400 mg of dietary NO3 −) and long-term (6 days) supplementation of amaranth concentrate derived dietary NO3 − on aerobic capacity in physically active young people. Methods We conducted a randomized, double-blind, placebo-controlled human study. Thirteen healthy and physically active young male participants were randomized into experimental and placebo groups. The aerobic capacity was tested during increasing cycling exercise (ICE) with pulmonary gas exchange recording and analysis. Results The peak power of the ICE, the maximum oxygen consumption and the first ventilatory threshold were significantly increased after long-term consumption of dietary amaranth (from 4.44 ± 0.50 to 4.55 ± 0.43 W/kg; from 37.7 ± 2.7 to 41.2 ± 5.4 mL/kg/min and from 178.6 ± 30.3 to 188.6 ± 35.2 W, p < 0.05; respectively) in experimental group. Conclusions Long-term (6 days) use of dietary NO3 − from amaranth may improve the aerobic capacity during ICE in young physically active male persons. It can be recommended as the nutritional supplement during last week of preparation for competition in endurance events.